PEMBUATAN NANOPARTIKEL-PERAK EKSTRAK DAUN UBI JALAR ORANGE (Ipomoea batatas L.) DENGAN METODE BIOREDUKSI DAN UJI AKTIVITAS TERHADAP JUMLAH TROMBOSIT Mus musculus - Ririn Trinanda; Agus Sundaryono; Dewi Handayani (University of Bengkulu, 2019)
This study aims to make silver nanoparticles (NPP) of orange Sweet potato extract (Ipomoea batatas L.) using bioreduction method and test the effect of giving silver nanoparticles - leaf extract of Ipomoea batatas L. orange (Ipomoea batatas L.) to the number of thrombocyte from male of Mus musculus induced by aspirin. The precursor used is 1 mM AgNO3 solution and as bioreductor is an antioxidant compound in orange sweet potato extract (Ipomoea batatas L.). The ratio of AgNO3 1 mM solution volume and orange sweet potato leaf extract is 9: 1 with 2 hours time. The characteristic test again obtained NPP is done using FTIR and Particle Size Analyzer (PSA) using Dynamyc Light Scattering method (DLS). The results showed that from the PSA analysis is known the average size of NPP – I. Batatas, L leaf extract is an average of 86.0 nm with a polydispersity value (PDI) of 0.17 < 1 that indicates that the NPP-leaf extract particle size distribution It is less homogeneous and are less stable.The results show that the administration of silver nanoparticles - orange sweet potato extract (Ipomoea batatas L.) can increase the platelet count of male mice significantly Dose of 0.014 g / Kgbb of 259,600 / mm3.